Application research of multi-finger robot hand grasping based on three-dimensional point cloud - ZHAN Hong; HUANG Jiebin; YANG Chenguang (Jixie chuandong)
ObjectiveIn the field of industrial manufacturing, the grasping action is the basis for robots to complete complex tasks. Therefore, it is very important to realize accurate perception and grasping of unknown and irregularly shaped objects for robots. A robot grasping experimental platform was built, and a grasping planning method based on multi-angle visual information was proposed.MethodsFirstly, a depth camera was used to collect the point cloud image of the unknown object from multiple views, and it was reconstructed in three dimensions to obtain the position and shape information of the unknown object. Then, the Gaussian process was utilized to fit the hidden surface of the unknown object, and the robot dynamic grasping planning scheme based on the attractor motion was used to realize the customized grasping.ResultsThe proposed grasping planning scheme was verified by the experiments to have the characteristics of fast speed, high precision and strong adaptability, and can meet the requirements of different environments and tasks, which is of great significance for practical application research related to robotics.